A high throughput gold nanoparticles chemiluminescence detection of opioid receptor antagonist naloxone hydrochloride - Alarfaj, Nawal A (Chem Cent J, 2015)
BACKGROUND: The opioid antagonist agent naloxone hydrochloride (NLX) is a drug that has high affinity for opiate receptors but do not activate these receptors. Owing to the role of this drug to block the effects of exogenous administered opioids and endogenous released endorphians we can deduce the importance of developing sensitive analytical methods for detection of such drug. In the present study gold nanoparticles (AuNPs) was employed for enhancing the chemiluminescence (CL) signals arising from luminol-ferricyanide reaction in the presence of naloxone hydrochloride using sequential injection chemiluminescence analysis (SIA). METHOD: In the present study gold nanoparticles (AuNPs) was employed for enhancing the chemiluminescence (CL) signals arising from luminol-ferricyanide reaction in the presence of naloxone hydrochloride using sequential injection chemiluminescence analysis (SIA). RESULTS: The developed method was examined under optimum experimental conditions and the obtained results revealed a linear relationship between the relative CL intensity and the investigated drug at a concentration range of 1.0×10(−9)-1.0×10(−2) mol L(−1), (r = 0.9993, n=9) with detection and quantification limits of 1.6×10(−11) and 1.0×10(−9) mol L(−1), respectively. The relative standard deviation was 0.9%. CONCLUSION: The proposed method was employed for the determination of the investigated drug in bulk powder, its pharmaceutical dosage forms and biological fluids. The interference of some metals and amino acids on the CL intensity was investigated. Also the interference of some related pharmacological action drugs was tested. The obtained results of the developed method were statistically treated and compared with those obtained from other reported methods. [Figure: see text]